Management Power and Corporate Risk Taking: Evidence from China - Wang, Zhongyu (2022)
Abstract Corporate risk-taking is the degree to which a firm demonstrates its tolerance for the risks it faces in order to achieve high returns in the course of its business. Management power influences the choice of business strategy and the preference for risk taking. Corporate risk-taking is not only a matter of improving corporate performance and long-term growth, but also of accumulating social capital. Based on it, Chinese A-share listed firms from 2016 to 2020 are the research objects in this paper. Through both theoretical research and empirical study, this paper investigates the impact of the combined management power and six different dimensions of management power on corporate risk-taking. This provides an in-depth analysis of the mechanism of the role of managerial power on corporate risk-taking behavior. The results of the study show that combined management power, organization power, ownership power, expert power and reputation power have a significant inhibitory effect on the level of corporate risk-taking. This implies that in order to promote a positive level of corporate risk-taking and to accelerate the accumulation of corporate capital, the different latitudes of management power should be appropriately allocated. Different incentive schemes could be used to set up for management. Companies also need to choose their management with a dialectical perspective. This will enhance the level of corporate risk-taking and help to increase the value of the company in the long term.